THE EFFECT OF MSME PERCEPTIONS, HUMAN RESOURCES COMPETENCE AND ACCOUNTING UNDERSTANDING ON THE IMPLEMENTATION OF EMKM SAK - Zulfa Husnipiddin Maulani Permana; Muhammad Iqbal Alamsyah (Universitas Indonesia Membangun, 2022)
Based on the results of the partial test (t test) it shows that the perception of MSME actors has a positive and significant effect on the implementation of SAK EMKM where the t-count > t-table is 2.732 > 1.672. Accounting understanding has a positive and significant effect on the implementation of SAK EMKM where the value of t-count > t-table is 5.379 > 1.672. Based on the results of the simultaneous test (F test) shows that the Perception of MSME Actors, Human Resources Competence, and Accounting Understanding simultaneously or together have a significant influence on the implementation of SAK EMKM, this is evidenced by the F-count > F-table, which is 38.763 > 2.77